2013
DOI: 10.1002/lary.23678
|View full text |Cite
|
Sign up to set email alerts
|

Intratympanic steroid therapy in moderate sudden hearing loss: A randomized, triple‐blind, placebo‐controlled trial

Abstract: The mean PTA recorded after the first-line approach (T1) demonstrated a significant therapeutic action of the short-duration intratympanic steroid therapy on moderate ISSNHL, with a flat audiogram shape, compared to the natural course of the disease and the placebo effect at that time point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 20 publications
(40 reference statements)
1
70
0
1
Order By: Relevance
“…Although this concentration is lower than those used in prior publications (i.e., 12-62.5 mg/mL dexamethasone or 40 mg/mL methylprednisolone) for IT [Battaglia et al, 2014;Filipo et al, 2013;Seggas et al, 2011], there is still no consensus about the appropriate concentration or injection schedule for IT in SSNHL [Stachler et al, 2012]. Because the only commercially available concentration of dexamethasone in Korea is 5 mg/mL, several previous studies conducted in Korea have used the same dexamethasone concentration [Ahn et al, 2008;Kim et al, 2012;Lee et al, 2010;.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Although this concentration is lower than those used in prior publications (i.e., 12-62.5 mg/mL dexamethasone or 40 mg/mL methylprednisolone) for IT [Battaglia et al, 2014;Filipo et al, 2013;Seggas et al, 2011], there is still no consensus about the appropriate concentration or injection schedule for IT in SSNHL [Stachler et al, 2012]. Because the only commercially available concentration of dexamethasone in Korea is 5 mg/mL, several previous studies conducted in Korea have used the same dexamethasone concentration [Ahn et al, 2008;Kim et al, 2012;Lee et al, 2010;.…”
Section: Discussionmentioning
confidence: 71%
“…Previous reports including systematic reviews and meta-analyses have concluded that isolated initial IT steroids can be a valuable solution for patients with SSNHL who either cannot tolerate systemic steroid therapy or are refractory to it [Filipo et al, 2013;Seggas et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, almost all of the patients presented an up-sloping audiometric curve, known to be the curve with a higher spontaneous recovery rate [Mattox and Simmons, 1977]. Moreover, in a recent randomized triple-blind placebo-controlled trial it has been demonstrated that there was a statistical significance of the therapeutic action of the IT steroid therapy on moderate ISSNHL with flat audiogram shape compared to the natural course of the disease and to the placebo effect [Filipo et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…SSNHL is generally unilateral, isolated and with variable clinical features in terms of hearing loss degree, accompanying symptoms and post-treatment outcomes. It was estimated that approximately half of SSNHL patients has a complete and spontaneous hearing recovery (Wilson et al, 1980;Filipo et al, 2013) even if a short course of corticosteroids is generally prescribed (Kuhn et al, 2011).…”
Section: Introductionmentioning
confidence: 99%